THE INFLUENCE OF MARKETING CAPABILITIES AND DIGITAL MARKETING ON THE MARKETING PERFORMANCE OF MSMEs FISH MILLING IN BENGKULU CITY - Kiasati, Kanaya Zharfa; Reswita, Reswita; Priyono, Basuki Sigit; Rahayu, Heni Sulistyawati Purwaning (Jurnal Perikanan Unram, 2025)
Bengkulu is a potential area in the capture marine fisheries business, the average yield of capture fisheries in Bengkulu City reaches 83338 tons. The potential for abundant results has a positive impact, namely many MSMEs have sprung up to utilize sea catches, one of which is a fish milling business in Bengkulu City. Changes in the business environment and technological developments, and technological developments require MSMEs to adopt digital technology and conduct digital marketing. By adopting digital technology, it is hoped that it will improve the marketing performance of fish milling MSMEs. This study aims to determine how marketing capabilities, digital marketing, and marketing performance and their effect on marketing performance. The data analysis method was carried out quantitatively and SEM PLS with 40 MSMEs as samples. The results showed that the marketing capabilities, digital marketing, and marketing performance of MSMEs were quite good. In addition, marketing capabilities and digital marketing have an effect on marketing performance.